On the Validity of Adipogenic Cell Lines as Model Systems for Browning Processes: In Authentic Brown, Brite/Beige, and White Preadipocytes, There is No Cell-Autonomous Thermogenic Recruitment by Green Tea Compounds - Otton, Rosemari; Petrovic, Natasa; Cannon, Barbara; Nedergaard, Jan (Frontiers in Nutrition, 2021)
The potential ability of nutritional compounds to induce or enhance browning of adipocytes has attracted large interest as a workable means of combatting the obesity epidemic. Green tea compounds are discussed as such inducers of an enhanced thermogenic capacity and activity. However, cell autonomous effects of green tea compounds on adipocytes have until now only been demonstrated in adipogenic cell lines (3T3-L1 and 3T3-F442A), i.e. cells of undefined tissue lineage. Here we examine the ability of green tea compounds to cell-autonomously induce thermogenic recruitment in authentic brown and brite/beige adipocytes in vitro. In primary brown adipocytes, the green tea compounds suppressed basal UCP1 gene expression, and there was no positive interaction between the compounds and adrenergic stimulation. In white adipocytes, green tea compounds decreased both basal and norepinephrine-induced UCP1 mRNA levels, and this was associated with suppression of cell differentiation, indicated by reduced lipogenic gene expression and lipid accumulation. A lack of interaction between rosiglitazone and green tea compounds suggests that the green tea compounds do not directly interact with the PPAR pathway. We conclude that there is a negative effect of the green tea compounds on basal UCP1 gene expression, both in brown and white primary adipocytes, in contrast to the positive effects earlier reported from studies in adipogenic cell lines. We point to the fact that the epigenetic status of the adipogenic cell lines is fundamentally different from that of genuine brown and white adipocytes, reflected e.g. in several-thousand-fold differences in UCP1 gene expression levels. Thus, results obtained with adipogenic cell lines cannot unreservedly be extrapolated as being relevant for authentic brown and white adipocytes in situ. We suggest that this conclusion can be of general concern for studies attempting to establish physiologically relevant cell autonomous effects.